Education in rural areas: A statistical approach - Corina-Georgeta Dinculescu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
An overall picture of the education system in the countryside reveals that there are still schools that are not connected to the drinking water and sewerage systems, where the toilet is in the school yard. There are still schools where children stay in classrooms dressed up with outdoor clothing in winter, with caps and gloves, due to inadequate heating and outdated school infrastructure. The simultaneous learning system is still in place (due to the relatively small number of enrolled pupils, which is steadily declining); this system does not benefit pupils, on the contrary, as these do not have the full attention and guidance of the teacher, as is the case in normal classes, they fail to acquire knowledge and skills, like those who study in the normal system, and thus they are disadvantaged. Due to the misunderstanding of the major importance that education has in in personal development of individuals and of society implicitly, there are not few schools that do not benefit from funding, support or interest from local councils. The local councils do not provide support either in terms of ensuring adequate infrastructure for a quality education or at least comparable to that in the urban area - clean classrooms, endowed with specific equipment for each subject of study, equipped with utilities (heating, indoor toilets, water), or in terms of supporting teachers in rural areas who do not have the residence there (by paying for transport, for instance). Local councils do not find or are not interested in finding levers to attract teaching staff in rural localities.In this context, the present paper aims to analyse the current situation (latest data available) of education in the rural area, using specific indicators, in terms of the education system resources and population's participation in education, such as: participation rate in education, school population, by levels of education and residence areas, classrooms/laboratories/workshops/gyms/sports fields/PC/IT equipment, by levels of education and residence areas, number of graduates by levels of education and residence areas.
Keywords: I21; I24; I25; R10; 330; education; disparities; residence areas; rural; urban